IMPROVING THE STUDENTS’ WRITING ABILITY IN NARRATIVE TEXT THROUGH PRAISE-QUESTION-POLISH (PQP) TECHNIQUE - Hasnawati Latif (Universitas Muhammadiyah Makassar, 2014)
The research aimed at improving the ability of the eighth year students of SMP Negeri 33 Makassar to write narrative text in terms of organization and language use by using Praise-Question-Polish (PQP) Technique. For the purpose, this research employed Classroom Action Research in which the researcher worked in planning, implementation of action, observation, and reflection on the data collected from the teaching and learning process and the students' writing products. The subjects of this research were 30 students of the first year students of SMP Negeri 33 Makassar in the academic year 2012/2013. The study was conducted in the diagnostic test and two cycles, each cycle was carried out in four meetings. The findings indicated that using Praise-Question-Polish (PQP) Technique could improve the students' ability in writing narrative text. Before giving implementation the researcher gave the students diagnostic test and the mean score of diagnostic test was 40,2 (Poor). Then the researcher conducted the cycle 1 and the cycle 2, and the result showed that the students' scores in the cycle 1 and cycle 2 improved. In cycle 1, the mean score of students was 68,7(Fair), meanwhile, the mean score of students in cycle 2 was 80,2 (Fairly good). The score of students’ writing in term of the organization in d-test was 50,4 (Poor) but after application of PQP ( Praise-Question-Polish ) Technique the students’ score became 67,8 (Fair) in cycle I, whereas in cycle 2 the students’ score was 79 (Fairly Good). The score of students’ writing in term of language use in d-test was 49,8 (Poor). In cycle I, it was improved became 69,4 (Fair) whereas in cycle 2 the students’ score was 80,7 (Fairly Good). The percentage of students’ participation in the first meeting of the cycle I was 65,8 % and it was improved became 82,5 % in the last meeting of cycle 2.Keywords: writing, organization, language use, Praise – Question- Polish